Implementation of Samsung Tech Institute Program in SMK Negeri 2 Bawang, Banjarnegara Regency - Hartantri, Anjuni Maulia; Linggarwati, Tundjung (JUSS (Jurnal Sosial Soedirman), 2024)
This research aims to determine the implementation of the Samsung Tech Institute Program which is Corporate Social Responsibility (CSR) from a multinational company, namely Samsung, especially at SMK Negeri 2 Bawang, Banjarnegara Regency. This research uses CSR as a framework analysis that uses the Triple Bottom Line principle. The method is a descriptive qualitative, with primary data sources from interviews and observations as well as secondary data. The research results show that the Samsung Tech Institute Program is implemented through Samsung Indonesia's CSR activities "Samsung Tech Institute" which has a selected curriculum such as Hand Held Product (HHP), Home Appliances (HA), Audio Visual (AV), Training of Teachers (ToT), Samsung Innovation Campus (SIC), Skills and Competency Test, and Field Work Practices. The implementation of the Samsung Tech Institute also contributes to produce the graduates who are able to compete in job competition.